CHARACTERIZATION IN ERNEST HEMINGWAY’S HILLS LIKE WHITE ELEPHANTS - AGNES, ADING PRADANI (Jurnal Ilmiah Mahasiswa FIB, 2014)
Agnes, Ading Pradani. 2014. Characterization in Ernest Hemingway’s Hills Like White Elephants. Study Program of English, Department of Languages and Literature, Faculty of Cultural Studies, Universitas Brawijaya. Supervisor: Sri Herminingrum; Co-supervisor: Melania Shinta HarendikaKeywords: Ernest Hemingway, short story, character, characterization.Short story is a medium to deliver the message of the author’s sense about what happened in society. Short story has the elements to reveal the author’s sense and one of them is character. Character as a sign is used to reflect the existence of the person in order to build the reader’s imagination, especially in the narrative text. Some of characters are presented by the author in direct or indirect characterization. Ernest Hemingway is a well known author who presents indirect characterization in his work. The characterization of each implicit character can be identified through the text in Hemingway’s Hills Like White Elephants.The study of Hemingway’s Hills Like White Elephants applies structuralismapproach as the grounding approach; generic form, and Roman Jakobson’smetaphor, and metonymy as the theories that are used to identify each character’s characterization through the texts and dialogues. Information about Hemingway and some references about characterization are needed to complete the process of identification.The result of this study presents Ernest Hemingway’s specialty in playing indirect characterization. In Hills Like White Elephants, Hemingway presents three indirect characters’ characterization; the American, the Girl and the Woman.Each character has traits. First, the characterization of the Girl shows that she is aperson who is always pessimistic with her condition, stubborn and she can becategorized as an emotionally unstable person. Second, the American’scharacterization shows that he is fickle, egoist, and he is also an irresponsibleperson. The last, the Woman’s characterization describes that she is a politeperson. For the further researchers, it is suggested to use historical approach inother Ernest Hemingway’s works because most of Hemingway’s works were fromhis experience during he spent his life in Europe by being the volunteer in WorldWar I.